2018
DOI: 10.21776/ub.jitek.2018.013.01.2
|View full text |Cite
|
Sign up to set email alerts
|

Optimasi Aktivitas Antioksidan Peptida Aktif dari Ceker Ayam Melalui Hidrolisis Enzim Papain

Abstract: The objective of this study was to optimization antioxidant activity of active peptides of chicken feet with papain hydrolysis. The research method was experimental design conducted using Factorial Completely Randomized Design. Treatments included papain concentration (control (0%) , 1%, 2% and 4%) and Incubation time (24 hours, 36 hours and 48 hours) were repeated four times. The variables observed were proximate analysis,microstructure, dissolved protein concentration and antioxidant activity. The results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
6
0
2
Order By: Relevance
“…The highest value was at CHP1 and the lowest was at CHP. Susanto et al (2018) reported that chicken feet protein hydrolysate using the papain enzyme had a dissolved protein content of 0.76-1.38 mg/ml determined by the Bradford method. This showed that chicken head protein hydrolysate using a combination of bromelain and papain has a higher soluble protein concentration compared to previous study.…”
Section: Soluble Protein Concentration Of Chicken Head Protein Hydrol...mentioning
confidence: 99%
“…The highest value was at CHP1 and the lowest was at CHP. Susanto et al (2018) reported that chicken feet protein hydrolysate using the papain enzyme had a dissolved protein content of 0.76-1.38 mg/ml determined by the Bradford method. This showed that chicken head protein hydrolysate using a combination of bromelain and papain has a higher soluble protein concentration compared to previous study.…”
Section: Soluble Protein Concentration Of Chicken Head Protein Hydrol...mentioning
confidence: 99%
“…Nilai IC 50 merupakan konsentrasi senyawa antioksidan yang memberikan inhibisi sebesar 50% yang artinya pada konsentrasi tersebut antioksidan dapat menghambat radikal bebas sebesar 50%. Nilai IC 50 berbanding terbalik dengan kapasitas antioksidan, artinya semakin kecil nilai IC 50 maka semakin tinggi kapasitas antioksidan sampel tersebut (Susanto, 2019). Pada kontrol positif asam askorbat didapatkan nilai IC 50 sebesar 6,9504 µg/mL, aktivitas antioksidannya sangat kuat karena merupakan larutan yang sudah murni.…”
Section: Pembahasanunclassified
“…The studies have been conducted related to the quality of meat and by product of local Indonesian livestock including chicken feet [2][3][4][5], Kacang goat [6]. There were several analyses used to characterize amino acids and bioactive peptides in foodstuffs, including using HPLC [7][8][9].…”
Section: Introductionmentioning
confidence: 99%